Manifesting smart tourism destinations: A study based on selected Himalayan cities in India - Jasrotia, Aruditya; Gangotia, Amit (Turyzm/Tourism, 2023)
In urban planning, the term smartness is considered as a philosophic dimension which enables smarter strategic decisions and directions. The involvement of information technology in the functioning of the daily life of cities is directed towards the development of smart cities. Smart tourism destinations can also implement smartness by employing suitable tourism applications within a smart city. The purpose of the study is to explore the enabling factors for establishing smart tourism destinations in the Indian Himalayas. This research used a qualitative methodology and conducted interviews with relevant stakeholders from the study areas, Jammu and Dharamshala. The data collected were recorded, transcribed and coded with the help of NVivo 12, in order to carry out thematic and content analysis. The findings of the study showcase that community welfare, information communication technology, quality of life, sociocultural heritage, stewardship, sustainable development and tourism resources are the enabling factors for smart tourism destinations in the context of the selected Himalayan cities in India. This study will be beneficial for destination managers for assessing destination smartness, and further, for researchers who want to study smart tourism destinations.